Clinical and radiological characteristics of ultrasonic humidifier lung and summer-type hypersensitivity pneumonitis. (November 2020) - Sakamoto, Susumu; Furukawa, Marie; Shimizu, Hiroshige; Sekiya, Muneyuki; Miyoshi, Shion; Nakamura, Yasuhiko; Urabe, Naohisa; Isshiki, Takuma; Usui, Yusuke; Isobe, Kazutoshi; Takai, Yujiro; Kurosaki, Atsuko; et al.
Abstract: Background: Ultrasonic humidifier lung is a rare form of hypersensitivity pneumonitis (HP), and its clinical and radiological features are unclear. This study examined the clinical and radiological characteristics of humidifier lung. Methods: Data from 18 patients with humidifier lung (mean age, 67.3 years) diagnosed during October 2012 through April 2018 were retrospectively reviewed. We compared clinical, laboratory, and CT findings and bronchoalveolar lavage fluid (BALF) characteristics of these patients with those of 19 patients with summer-type HP (mean age, 57.4 years). Results: Cough and dyspnea were the most common symptoms. White blood cell count and serum C-reactive protein titers were higher for humidifier lung than for summer-type HP. Serum levels of Krebs von den Lungen-6 and surfactant protein D were significantly lower for humidifier lung than for summer-type HP. The most common chest CT findings in humidifier lung were ground-glass opacities (88.9%) and mosaic attenuation (50.0%). Centrilobular ground glass nodules were less common in humidifier lung than in summer-type HP (27.8% vs 63.1%; P = 0.043). Peribronchovascular or subpleural nonsegmental consolidation was more frequent in humidifier lung than in summer-type HP (44.4% vs 5.3%; P = 0.013). Lymphocyte fractions in BALF specimens were significantly lower for humidifier lung than for summer-type HP (37.3% vs 69.0%; P < 0.001). Neutrophil fractions were higher for humidifier lung, but the difference was not significant (22.1% vs 8.1%; P = 0.153). The CD4/8 ratio was higher for humidifier lung than for summer-type HP (1.7 vs 0.8; P = 0.003). Conclusions: The clinical and radiological characteristics of humidifier lung differ from those of summer-type HP. Highlights: The clinical characteristics of humidifier lung differ from those of summer-type HP. Chest HRCT findings of humidifier lung differ from those of summer-type HP. The CD4/8 ratio of BALF was higher for humidifier lung than for summer-type HP.